EFEKTIVITAS TERAPI PERMAINAN JEMURAN BERNOMOR UNTUK MENINGKATKAN KEMAMPUAN MELAKUKAN PENGURANGAN BAGI ANAK TUNAGRAHITA RINGAN DI KELAS II SLB BASO KABUPATEN AGAM - Putri Setia Ningsih, Ganda Sumekar, Damri (Jurnal Penelitian Pendidikan Khusus, 2013)
The research was motivated by the problems that researchers found in SLB Baso Agam, of a child class II SLB second half is having problems in doing the reduction numbers 1-10. This research Single Subject Research approach, with desaian A-B-A. Results of this study indicate that the play therapeutic numbered clothespins effective in improving the ability to make cuts laterally series for children 1-10 grade II mild mental retardation SLB Baso Agam.